The relationship between monocarboxylate transporters 1 and 4 expression in skeletal muscle and endurance performance in athletes - Bentley, D. J.; Roels, B.; Thomas, C.; Ives, R.; Mercier, J.; Millet, G.; Cameron-Smith, D. (European Journal of Applied Physiology, 2009)
The purpose of this study was to examine the relationship between skeletal muscle monocarboxylate transporters 1 and 4 (MCT1 and MCT4) expression, skeletal muscle oxidative capacity and endurance performance in trained cyclists. Ten well-trained cyclists (mean ± SD; age 24.4 ± 2.8 years, body mass 73.2 ± 8.3 kg, VO2max 58 ± 7 ml/kgmin) completed three endurance performance tasks [incremental exercise test to exhaustion, 2 and 10 min time trial (TT)]. In addition, a muscle biopsy sample from the vastus lateralis muscle was analysed for MCT1 and MCT4 expression levels together with the activity of citrate synthase (CS) and 3-hydroxyacyl-CoA dehydrogenase (HAD). There was a tendency for VO2max and peak power output obtained in the incremental exercise test to be correlated with MCT1 (r = -0.71 to -0.74; P < 0.06), but not MCT4. The average power output (P average) in the 2 min TT was significantly correlated with MCT4 (r = -0.74; P < 0.05) and HAD (r = -0.92; P < 0.01). The P average in the 10 min TT was only correlated with CS activity (r = 0.68; P < 0.05). These results indicate the relationship between MCT1 and MCT4 as well as cycle TT performance may be influenced by the length and intensity of the task.